Lack of Association of Serum MMP-9 Concentration and rs17576 Single Nucleotide Variant MMP-9 Gene With the Degree of Coronary Atherosclerosis and Other Risk Factors in Ukrainian Patients With Coronary Artery Disease - Oksana S. Pogorielova; Viktoriia V. Korniienko; Yaroslav D. Chumachenko; Olha A. Obukhova; Yelizaveta A. Stroy; Viktoriia Yu Harbuzova (Cardiology Research and Practice)
This study probes the relationship between serum matrix metalloproteinase-9 (MMP-9) levels, the genetic variant rs17576 in the MMP-9 gene, and the extent of coronary atherosclerosis among Ukrainian patients diagnosed with coronary artery disease (CAD). A cohort of 128 patients was assessed, comprising 25 with angiographically intact (normal) coronary arteries, 40 with acute coronary syndrome (ACS), and 63 with chronic coronary syndrome (CCS). Utilizing clinical, anthropometric, and biochemical analyses, alongside ELISA immunoassays, genotyping, electrocardiography, and coronary angiography, we conducted a comprehensive evaluation. Our findings indicate that MMP-9 levels peaked in ACS patients, particularly those with single and triple-vessel coronary lesions, while the lowest levels were observed in individuals with unaltered coronary arteries. Notably, the glomerular filtration rate (GFR) was highest in patients with angiographically normal coronary arteries, averaging 79.91 ± 27.8 mL/min. In the context of ACS, individuals carrying the GG allele exhibited the highest GFR, whereas AA allele carriers had the lowest. Conversely, in the CCS cohort, GG carriers demonstrated the lowest GFR and heterozygotes the highest, although these differences did not reach statistical significance. A significant disparity in serum MMP-9 levels was observed between ACS patients, CCS patients, and individuals with unimpaired coronary arteries. Moreover, a substantial correlation was established between the degree of coronary artery lesions and GFR in the CCS group, providing a predictive measure for GFR in patients with triple-vessel involvement. However, no significant association was detected between serum MMP-9 levels, the rs17576 genetic variant in the MMP-9 gene, and the number of affected vessels or GFR in both ACS and CCS patients.